2009
DOI: 10.1021/ol902157c
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Aromatic C−O Bond Formation: Synthesis of 3-Functionalized Benzo[b]furans by FeCl3-Mediated Ring Closure of α-Aryl Ketones

Abstract: A variety of 3-functionalized benzo[b]furans were achieved by way of a FeCl(3)-mediated intramolecular cyclization of electron-rich alpha-aryl ketones. The alkoxy substituent on the benzene ring in the substrates was essential for an efficient cyclization to occur. This novel method allows the construction of benzo[b]furan rings by joining the O-atom on the side chain to the benzene ring via direct oxidative aromatic C-O bond formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(28 citation statements)
references
References 34 publications
0
27
1
Order By: Relevance
“…Chemie of oleate/oleylamine-capped CsPbBr 3 (OA/OAm-CsPbBr 3 ) perovskite QDs (Figure 1c). With different QDs in hand, we started with 2-(3,4dimethoxyphenyl)-3-oxobutanenitrile (1a)a samodel substrate to investigate the feasibility of photocatalytic coupling reactions using the QDs as photocatalysts.With two electrondonating methoxy groups on the phenyl ring, 1a has been reported to convert to benzo[b]furan via oxidative intramolecular cyclization [24] or to ad imer via oxidative intermolecular C À Cc oupling. [21,22] When 1a was treated with CdSe QDs passivated with surface ligands of trioctylphosphine (TOP), octadecylphosphonic acid (ODPA), trioctylphosphine oxide (TOPO), 99 %ofthe dimer (2a)product with negligible amount of benzo[b]furan was obtained after 44 ho fi rradiation using ab lue LED light source (435-445 nm) ( Table 1, Entry 1).…”
Section: Methodsmentioning
confidence: 99%
“…Chemie of oleate/oleylamine-capped CsPbBr 3 (OA/OAm-CsPbBr 3 ) perovskite QDs (Figure 1c). With different QDs in hand, we started with 2-(3,4dimethoxyphenyl)-3-oxobutanenitrile (1a)a samodel substrate to investigate the feasibility of photocatalytic coupling reactions using the QDs as photocatalysts.With two electrondonating methoxy groups on the phenyl ring, 1a has been reported to convert to benzo[b]furan via oxidative intramolecular cyclization [24] or to ad imer via oxidative intermolecular C À Cc oupling. [21,22] When 1a was treated with CdSe QDs passivated with surface ligands of trioctylphosphine (TOP), octadecylphosphonic acid (ODPA), trioctylphosphine oxide (TOPO), 99 %ofthe dimer (2a)product with negligible amount of benzo[b]furan was obtained after 44 ho fi rradiation using ab lue LED light source (435-445 nm) ( Table 1, Entry 1).…”
Section: Methodsmentioning
confidence: 99%
“…of oleate/oleylamine-capped CsPbBr 3 (OA/OAm-CsPbBr 3 ) perovskite QDs (Figure 1c). With different QDs in hand, we started with 2-(3,4dimethoxyphenyl)-3-oxobutanenitrile (1a)a samodel substrate to investigate the feasibility of photocatalytic coupling reactions using the QDs as photocatalysts.With two electrondonating methoxy groups on the phenyl ring, 1a has been reported to convert to benzo[b]furan via oxidative intramolecular cyclization [24] or to ad imer via oxidative intermolecular C À Cc oupling. [21,22] When 1a was treated with CdSe QDs passivated with surface ligands of trioctylphosphine (TOP), octadecylphosphonic acid (ODPA), trioctylphosphine oxide (TOPO), 99 %ofthe dimer (2a)product with negligible amount of benzo[b]furan was obtained after 44 ho fi rradiation using ab lue LED light source (435-445 nm) ( Table 1, Entry 1).…”
Section: Forschungsartikelmentioning
confidence: 99%
“…Yu reported the oxidative approach to dihydrobenzofurans 2 from alcohols 1 via Pd(II)-catalyzed and hydroxyl-directed C-H bond activation followed by C-O bond formation [18]. Zhao reported that FeCl 3 -mediated oxidative aromatic C-O bond forming cyclization of ketones 3 gave the benzofurans 4 [19].…”
Section: Introductionmentioning
confidence: 99%